2018
DOI: 10.4172/2378-5756.1000442
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Psychiatric Disorders in Alcohol Dependence: A Control Study

Abstract: Background: Though anecdotal evidence of comorbid psychiatric disorders in alcohol dependent patient abound there is lack of systematic Indian studies in this area. Aim: To determine the type and frequency of comorbid psychiatric disorders in alcohol dependent individuals as compared with matched normal population. Methods: This cross-sectional, hospital based, utilized the Mini International Neuropsychiatric Interview to assess 88 alcohol-dependent patients consecutively admitted to de-addiction unit of two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…[10] In our study the comorbidity rate was 45.16 % of which all were Axis I disorders. This prevalence is similar to that of the studies by Chaudhary S. et al [9] (46.59%) and Singh A. et al [12] A French hospital based study by Nubukpo P. et al [13] also reported a similar prevalence of 42.12%. However, this figure is lower than that of the studies by Vohra AK et al [11] and Kumar V. et al [14] in which the prevalence were 76.6% and 64.8% respectively.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…[10] In our study the comorbidity rate was 45.16 % of which all were Axis I disorders. This prevalence is similar to that of the studies by Chaudhary S. et al [9] (46.59%) and Singh A. et al [12] A French hospital based study by Nubukpo P. et al [13] also reported a similar prevalence of 42.12%. However, this figure is lower than that of the studies by Vohra AK et al [11] and Kumar V. et al [14] in which the prevalence were 76.6% and 64.8% respectively.…”
Section: Resultssupporting
confidence: 90%
“…In addition, comorbid psychiatric disorders in alcohol dependence are associated with prolonged hospital stay, poor treatment outcomes, higher relapse rates, suicide, homelessness, and negative impact on family. [9] Alcohol is one of the commonest drugs of abuse in Nepal. Yet, published literature on alcohol dependence and comorbidities is scarce in Nepal.…”
mentioning
confidence: 99%